Antilisterial activity of bacteriocinogenic Pediococcus acidilactici HA6111-2 and Lactobacillus plantarum ESB 202 grown under pH and osmotic stress conditions - Engelhardt, Tekla (2016)
Bacteriocin producing lactic acid bacteria (LAB) cultures can be used as biopreservatives in fermented food products; thus the food industry is interested in stable cultures that produce bacteriocins consistently. Inhibtion of Listeria spp. by bacteriocinogenic Pediococcus acidilactici and Lactobacillus plantarum (both isolated from fermented meats) was investigated under conditions of stress induced by low pH and high salt concentrations. Listeria monocytogenes serogroup IIb (from cheese), L. monocytogenes serogroup IVb (from cheese), L. monocytogenes serogroup IIb (from ground beef) and Listeria innocua NCTC 11288 were used as target strains. P. acidilactici and Lb. plantarum demonstrated antilisterial activity under the stress conditions investigated (pH 3.5; pH 8.5; 7.5% NaCl). However, activity was dependent on the stress conditions applied and on the target organism. L. monocytogenes serogroup IIb (from ground beef) and L. innocua C 11288 were, respectively the most sensitive and the most resistant to the cell-free supernatants produced by the LAB investigated.